Gender and Economic Development in Millennium Challenge Corporation Indicators: An Assessment and Recommendations - Bi, Xiaojia; Duffy, Mariah Quinn; Rimal, Bickey; Thorngate, Kelly; Trembley, Andrew (My University, 2011)
The Millennium Challenge Corporation, a U.S. agency that dispenses foreign aid to promote development in low-income and lower-middle income countries, reviews its indicators and methodology annually and then implements changes. This report analyzes the gender sensitivity of current and potential indicators for evaluating applicant countries. This report proposes modification of four indicators and creation of four indicators for the MCC to promote gender equality as a meaningful investment in economic development.